Atomically Dispersed Pd-O Species on CeO2(111) as Highly Active Sites for Low-Temperature CO Oxidation - Spezzati, Giulia; Su, Yaqiong; Hofmann, Jan P; Benavidez, Angelica D; DeLaRiva, Andrew T; McCabe, Jay; Datye, Abhaya K; Hensen, Emiel J M (ACS catalysis, 2017)
Ceria-supported Pd is a promising heterogeneous catalyst for CO oxidation relevant to environmental cleanup reactions. Pd loaded onto a nanorod form of ceria exposing predominantly (111) facets is already active at 50 °C. Here we report a combination of CO-FTIR spectroscopy and theoretical calculations that allows assigning different forms of Pd on the CeO2(111) surface during reaction conditions. Single Pd atoms stabilized in the form of PdO and PdO2 in a CO/O2 atmosphere participate in a catalytic cycle involving very low activation barriers for CO oxidation. The presence of single Pd atoms on the Pd/CeO2-nanorod, corroborated by aberration-corrected TEM and CO-FTIR spectroscopy, is considered pivotal to its high CO oxidation activity.Ceria-supported Pd is a promising heterogeneous catalyst for CO oxidation relevant to environmental cleanup reactions. Pd loaded onto a nanorod form of ceria exposing predominantly (111) facets is already active at 50 °C. Here we report a combination of CO-FTIR spectroscopy and theoretical calculations that allows assigning different forms of Pd on the CeO2(111) surface during reaction conditions. Single Pd atoms stabilized in the form of PdO and PdO2 in a CO/O2 atmosphere participate in a catalytic cycle involving very low activation barriers for CO oxidation. The presence of single Pd atoms on the Pd/CeO2-nanorod, corroborated by aberration-corrected TEM and CO-FTIR spectroscopy, is considered pivotal to its high CO oxidation activity.